Bearing capacities of single piles under combined HM loading near slopes - Bian, Meihua; Peng, Jianing; Zhang, Xingsen; Li, Junhua; Qin, Songlin (Frontiers in Materials, 2023)
Piles are widely used to transfer horizontal load of high-rise buildings, transmission towers, and bridges, and especially for the superstructures constructed near slopes. This study investigated bearing capacities of single piles under combined horizontal force (H) and bending moment (M) for the pile in the sloping ground. A 3D finite element model was proposed to simulate the nonlinear pile - soil interaction and was verified by a model test. A series of numerical tests were conducted to obtain the failure envelope of bearing capacities of single piles under various combinations of H and M. The existence of slope significantly reduced the bearing capacity of piles, especially when the horizontal and rotational displacements moved to the dip direction of the slope. An oblique ellipse was able to describe the failure envelope of bearing capacities of single piles near slopes in the HM plane. As the pile installed away from the crest of the slope, both the width and height of the ellipse increased and the center of the ellipse was approaching to the origin. The results of this paper can provide useful references for designing horizontally loaded piles near slopes.